PENILAIAN FINANCIAL PERFORMANCE PERUSAHAAN MANUFAKTUR KIMIA DITINJAU DARI LIKUIDITAS, SOLVABILITAS DAN COMMON SIZE - Arinda, Nadya Tri; Nurdiwaty, Diah; Tohari, Amin (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2023)
This study aims to determine the effect of liquidity ratios, solvency ratios and common size financial performance both partially and simultaneously on chemical manufacturing entities listed on the IDX 2018-2022. Comparative causal quantitative techniques. The sample in this study are chemical manufacturing entities listed on the IDX 2018-2022 that have met the criteria. The conclusion from this study is that Liquidity and Common Size partially affect the financial performance of chemical manufacturing companies listed on the IDX in 2018-2022. Partially, solvency has no effect on the financial performance of chemical manufacturing companies listed on the IDX in 2018-2022. Liquidity, Solvency, and Common Size in profit and loss simultaneously affect the financial performance of chemical manufacturing entities listed on the IDX 2018-2022.